y = 2x + 2
Пошаговое объяснение:
Мы знаем, что уравнение касательной в точке представимо в виде
Подставим:
f(x) = 6x - 2x²; x₀ = -1
уравнение касательной
y = f'(-1) (x-(-1)) +f(-1)
f(-1) = -6 -2 = -8
f'(x) = 6-4x; f'(-1) = 10
уравнение касательной в точке х₀=(-1) имеет вид
у = 10х +2
y = 2x + 2
Пошаговое объяснение:
Мы знаем, что уравнение касательной в точке
представимо в виде ![y = f(x_0) + f'(x_0)\cdot(x - x_0)](/tpl/images/1353/1615/2da13.png)
Подставим:![y = (-2\cdot(-1)^{2} + 6\cdot(-1)) + (-4\cdot(-1) + 6)\cdot(x - 1) = -4 + 10\cdot(x - 1) = 10x - 14](/tpl/images/1353/1615/ebd4e.png)
Пошаговое объяснение:
f(x) = 6x - 2x²; x₀ = -1
уравнение касательной
y = f'(-1) (x-(-1)) +f(-1)
f(-1) = -6 -2 = -8
f'(x) = 6-4x; f'(-1) = 10
уравнение касательной в точке х₀=(-1) имеет вид
у = 10х +2